Diversity and temporal distribution of birds in rice-growing landscape,Northern Peninsular Malaysia - Nur Munira, A.; Nurul Salmi, A.L.; Shahrul Anuar, M.S.; Mohd Abdul Muin, M.A.; Amirrudin, A.; Nur Juliani, S. (Universiti Kebangsaan Malaysia, 2014)
Rice fields are traditional landscape in Malaysia that sustains various species of birds. Waterbirds, raptors, Passeriformes and Columbiformes were observed and counted using point count method at rice fields in Bandar Baharu, Kedah from March 2009 to February 2010. The current status of birds in the rice fields of Malaysia has not been widely researched. The objective of this study was to document the bird species richness and diversity and temporal bird distribution during the annual rice growing cycle. There were 5120 birds representing 67 species belonging to 29 families being recorded. The diversity index (Shannon-Wiener) varied monthly between 2.154 and 3.321. The most abundant bird family observed was Ardeidae (29.09%), followed by Sturnidae (10.15%) and Hirundinidae (7.86%). Rice growing seasons involve three main stages; direct seedling/transplanting, growing and harvesting. Each stage attracts different bird species to exist in the rice field and surrounding areas. Statistical analysis showed the alternative hypothesis that states abundance of bird species is different monthly was accepted (F11, 24 = 3.033, p< 0.05). Farming activities and rice growing seasons regularly influenced birds’ presence in the rice fields and attracted different bird species. Reclamation and urban development on the rice fields is a major concern. Conservation efforts and strict regulation of pesticide use should be implemented to develop sustainable agriculture practices that are beneficial to human and wildlife communities.